Students’ Meta-Cognitive Learning Strategies Toward Speaking Proficiencyin EFL Class - Ika Handayani; Siti Aisah (Bandar Lampung University (UBL), 2013)
This writing is a report of a minor research conducted to find out students’ meta-cognitive learning strategies toward their speaking proficiency and investigate some barriers in applying the meta-cognitive strategies toward their grammatical, strategic, discourse and sociolinguistic competencies. The meta-cognitive learning strategies itself, in this research, refers students’self-reflection, self-responsibility and initiative, as well as goal setting and time management,(Hismanouglu,2000). Oxford (1990) adds that meta-cognitive learning strategies include recognizing when a strategy is needed, selecting strategies, memorizing or rehearsing strategies, and assessing the helpfulness of strategies. So, in this study, the researchers limits on what kind of meta-cognitive learning strategies that the students use to encounter some problems in learning speaking toward their speaking proficiency and the barriers that they find in applying the strategiesinclude in meta-cognitive strategies. This idea, in line with the theory from Oxford (1990) about three majors strategies in learning English as foreign language: centering the learning, arranging and planning the learning and evaluating the learning. The researchers tried to focus in the students’ meta-cognitive strategies toward their speaking proficiency: grammatical competencies, strategic competencies, discourse competencies and sociolinguistic competencies. It means that the researchers elaborate the students’ meta-cognitive learning strategies in mastering those four competences in speaking proficiency. As it is a case study, the researcher involved ten students in the speaking 4 class at the English education department. The choice of these subjects is based on their speaking fluency which is better than other friends in the classroom. This is important choosing the ten students, because in implementing meta-cognitive learning strategies, the students should have better ability in finishing their speaking tasks.. The data were collected through classroom observation, informal talk with the lecturer and interview with students (ten students). Further, the data analysis was conducted qualitatively and done over the course of the study. On going data analysis and interpretations were based mainly on observation notes (note taking), informal conversations (interview)with both lecturer and students. And, the data analysis was done through expert judgment and theory which is using triangulation intechniques and source. Results of this study reveal that most of the students (70%) centered their learning before the lecturer explaining the tasks. There were 50 % students who arranged and planned their learning in accomplishing their tasks. However , the students did not apply all six minor strategies of the second major in meta-cognitive learning strategies,. They skipped “identifying the purpose of the task and setting the objective of the learning of tasks”. There were 50% students who applied the last strategy in mata-cognitive learning strategies, evaluating their learning by having self monitoring and self evaluation. In terms of barriers toward speaking profiency, the interview conducted show that the students got barriers in discourse and strategic competence that refers to the ability to keep communication in meaningful way, to know when and how to take the floor, how to keep a conversation going, how to terminate the conversation and how to clear up the communication break down as well as comprehension problems.